Timely Diagnosis of Colorectal Cancer (Springer International Publishing, 2018)
This book summarizes current knowledge and outlines directions for the future on how to improve the art of diagnosing colorectal cancer with emphasis on timeliness, one of the most vital issues in cancer management. Using a comprehensive, multi-disciplinary approach, it provides an overview of decisive factors in timely diagnosis of colorectal cancer from symptom scores and symptom awareness to technical aspects. The book starts by discussing early diagnosis from the perspective of patients, including the importance of awareness in the general population as well as psychological aspects. It then goes on to discuss issues of importance to clinicians, such as fast tracking, laboratory testing, improving technical skills and optimizing endoscopy services. In addition, more practical issues such as cost-effectiveness and auditing are also extensively discussed. By focusing on one specific but common form of cancer the content translates well across the scope of other cancer types and can be used by professionals working on different cancer types. This book provides clinicians, clinical researchers and policymakers with a comprehensive overview of the field of timeliness in diagnosing colorectal cancer. By addressing the challenges posed in the management of symptomatic patients it informs and educates the experts and could help improve diagnosis.